Implementation and Evaluation of 5G Standalone Network Using Open5GS, srsRAN, and USRP B210 for Research Purposes - Noviansyah, Noer Ramadhon; Aryanti, Aryanti; Sopian Soim (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
This study aims to implement and evaluate an Open Source-based 5G Standalone (SA) network using Open5GS as the Core Network, srsRAN as the Radio Access Network (RAN), and USRP B210 as a Software Defined Radio (SDR) device. A commercial smartphone was used as the User Equipment (UE) to test end-to-end network connectivity and performance. The research method includes software installation, network parameter configuration, system integration, as well as connectivity and performance testing based on ITU-R IMT-2020 standards. The test results show that all network elements were successfully integrated, as indicated by the successful registration and authentication of the UE and the establishment of a data session. Performance testing recorded a downlink throughput of 55 Mbps, uplink throughput of 15 Mbps, latency of 33 ms, jitter of 8.9 ms, and 0% packet loss. Although some performance parameters did not meet the minimum ITU-R IMT-2020 standards, the system proved operable as an independent Open Source and SDR-based solution for experimental purposes in a laboratory environment. Future work should focus on optimizing the backhaul connection, conducting multi-UE testing, and simulating mobility and handover scenarios to assess system performance in large-scale and real-world deployments.